Use of Phosphorus Binders among Non-Dialysis Chronic Kidney Disease Patients and Mortality Outcomes - Bhandari, Simran K; Liu, In-Lu A; Kujubu, Dean A; Huynh, Trung; Behayaa, Hind; Kovesdy, Csaba P; Kalantar-Zadeh, Kamyar; Jacobsen, Steven J; Sim, John J (American journal of nephrology, 2017)
Whether the benefits of phosphorus binders extend to those without end stage renal disease is uncertain. Among a large diverse non-dialysis chronic kidney disease (CKD) population with hyperphosphatemia, we sought to evaluate phosphorus binder use and compare mortality risk between patients prescribed and not prescribed binders. A retrospective cohort study within an integrated health system (January 1, 1998 - December 31, 2012) among CKD patients (age ≥18) was performed. Non-dialysis CKD patients with 2 separate estimated glomerular filtrate rate (eGFR) <30 mL/min/1.73 m2 and serum phosphorus ≥5.0 mg/dL within 180 days of eGFR were included. Multivariable cox proportional hazards and inverse probability of treatment-weighted models were used to estimate mortality hazard ratios (HRs) for patients who received phosphorus binders compared to no binders. Among 10,165 study patients, 2,733 subjects (27%) received phosphorus binders. Compared to the no-phosphorus-binder group, the binder group had mortality HRs (95% CI) of 0.86 (0.79-0.94) and 0.86 (0.80-0.93) using traditional multivariable and inverse probability of treatment-weighted models respectively. Sensitivity analyses removing patients who were prescribed binders >180 days after index date revealed no difference in mortality between those with binders and with no binders. Our findings from a real-world clinical environment revealed that 27% of hyperphosphatemic non-dialysis CKD patients were prescribed binders. They also had lower risk of mortality compared to those not prescribed phosphorus binders. However, the lower mortality risk was not observed when we accounted for immortal time bias. Whether phosphorus binder use in CKD improves survival remains to be determined.